PENDAMPINGAN IMPLEMENTASI KURIKULUM 2013 MELALUI SULASTRI DI SMPN 15 BANJARMASIN - Arbainah Arbainah (FKIP ULM, 2020)
The 2013 Curriculum Implementation assistance activity is an essential first step to accelerate understanding and skills in implementing the curriculum. To maintain and improve the continuity, performance, and implementation of the 2013 curriculum in each education unit, a study was carried out to implement the 2013 curriculum through